Association of possible osteopetrosis with acute myeloid leukaemia in a child - Prasad, Rajniti (BMJ Publishing Group, 2013)
Osteopetrosis is a rare disease characterised by an increase in bone mass, skeletal malformations and bone marrow failure due to defective bone resorption. We report a 3-month-old male child presented with chest infections, failure to thrive and hepatosplenomegaly and diagnosed with osteopetrosis associated with acute myeloid leukaemia M(3) type (AML-M(3)). The patient died on day 7 of admission due to respiratory failure. To our knowledge, this is the first case where both osteopetrosis and AML is diagnosed in a patient.